Impact of Video vs. Leaflet Education on Parents' Knowledge and Attitudes Towards Stunting Prevention - Siti Fatimah; Arantika Meidya; Arif Sabta Aji; Hamdhoona Abdullah; Siti Nurunniyah (Jurnal Bidan Cerdas, 2026)
Background: Stunting is a significant health challenge, leading to health issues and impaired cognitive development in children, affecting the nation’s future human resources. While various educational interventions have been implemented, no evaluation has compared the effectiveness of different media for parents. This study aimed to evaluate the effectiveness of video and leaflet-based education for mothers and fathers of toddlers at risk of stunting. Methods: A quasi-experimental pretest-posttest one-group design was used. The sample consisted of 120 parents, divided into an intervention group (video) and a control group (leaflet), selected by simple random sampling. Multiple regression analysis was created to examine the association. Results: Significant pretest-posttest improvements in knowledge and attitudes were observed in both parents (p <0.05). Logistic regression analysis showed that video-based education positively influenced mothers' knowledge and attitudes, with education type being the only significant factor affecting mothers' knowledge. In fathers, video-based education increased knowledge, but no factors were found to affect attitudes. Conclusion: Both video and leaflet-based education effectively improved mothers' knowledge and attitudes. Video education enhanced fathers' knowledge but had no effect on their attitudes. These differences may reflect the greater attention and perception of stunting among mothers in the socio-cultural context of Indonesia.